2008
DOI: 10.3382/ps.2007-00207
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tomato Powder Supplementation on Performance and Lipid Peroxidation in Quail

Abstract: Recent studies have suggested a protective role for lycopene, an antioxidant carotenoid, in the prevention of stress including environmental stress. Tomatoes and tomato products are the major dietary source of lycopene. The objective of the present study was to investigate the effect of dietary tomato powder supplementation on the performance and lipid peroxidation of meat in Japanese quail (Coturnix coturnix japonica) exposed to a high ambient temperature of 34°C. A total of 180 ten-day-old male quails were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 41 publications
6
49
0
1
Order By: Relevance
“…This result is in agreement with the studies of Sahin et al (2008) and Patra et al (2011) who concluded that dietary natural antioxidants are the first strategy against the unpleasant consequences of heat stress on the quality of poultry meat. Moreover, the results revealed that the combination of BP and BG did not have a significant effect on CK level.…”
Section: Quinteirosupporting
confidence: 93%
“…This result is in agreement with the studies of Sahin et al (2008) and Patra et al (2011) who concluded that dietary natural antioxidants are the first strategy against the unpleasant consequences of heat stress on the quality of poultry meat. Moreover, the results revealed that the combination of BP and BG did not have a significant effect on CK level.…”
Section: Quinteirosupporting
confidence: 93%
“…However, some authors stated that because lycopene-rich foods contain a number of other beneficial phytonutrients, it is difficult to determine what proportion of their health-protective effects are attributable to lycopene (Hadley et al 2002). Since tomatoes and tomato products are the major dietary source of lycopene (Sahin et al 2008), lycopene can be considered as a biomarker for the additive or synergistic anticancer effects of their phytonutrients. Boileau et al (2003), supporting this observation, concluded that consumption of tomato powder but not lycopene inhibited prostate carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Sahin et al [32] found that MDA levels in muscles, liver and serum (0.65 vs. 0.07; 2.5 vs. 1.15 and 1.79 vs. 0,55; P=0.001) linearly decreased in birds with dietary tomato powder supplementation in all birds. There were interaction effects of temperature and tomato powder levels on serum (P=0.02), breast and leg muscles and liver MDA concentrations (P=0.001).…”
Section: Effects On Lipid Peroxidationmentioning
confidence: 94%